Aggressive combination therapy for treatment of systemic sclerosis-associated pulmonary hypertension. Issue 1 (February 2018) - Coghlan, JG; Denton, Christopher P.
Pulmonary arterial hypertension is an important complication of systemic sclerosis with high mortality but should be regarded as a treatable manifestation of the disease. Management draws on experience from other forms of pulmonary arterial hypertension and benefits from an increasing number of licenced therapies. Outcome is variable but recent clinical trials suggest that combination therapies used early in the disease may be associated with better outcomes. This is important because previous clinical trials using short-term gain in exercise capacity did not show significant benefit compared to that observed for idiopathic or heritable forms of pulmonary arterial hypertension. Thus, it is important to identify cases as early as possible and to manage cases that are in a high-risk group using early combination therapy. This review summarises the most recent analyses of clinical trial data, with a focus on those patients with SSc-associated pulmonary arterial hypertension and provides the evidence base that supports current treatment recommendations for aggressive pulmonary arterial hypertension occurring in systemic sclerosis, including the early use of combination pulmonary arterial hypertension–specific drugs in appropriate cases.